2023
DOI: 10.55522/jmpas.v12i2.4748
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication's knowledge and practice in adults attending pharmacies in Tripoli, Libya

Abstract: Self-medication is a widespread practice that may contribute to the antibiotic resistance of human pathogens. This study was aimed to determine the prevalence of self-medication among Libyan patients in Tripoli city. This descriptive, questionnaire- based cross-sectional study was conducted from August to October 2022 among Libyan patients in Tripoli city. The questionnaire was compromising from 13 questions. Three questions were dedicated to the general demographics and the next 10 questions were based on sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Our results also reported that the most frequently self-medicated drugs by the students were Augmentin (61 with 41.5%), followed by amoxicillin (54 with 36.7%) and Azithromycin (44 with 29.9%), which is also consistent with other published studies [8,14,18]. This may be because it is the most used and prescribed antibiotics by doctors globally.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results also reported that the most frequently self-medicated drugs by the students were Augmentin (61 with 41.5%), followed by amoxicillin (54 with 36.7%) and Azithromycin (44 with 29.9%), which is also consistent with other published studies [8,14,18]. This may be because it is the most used and prescribed antibiotics by doctors globally.…”
Section: Discussionsupporting
confidence: 92%
“…In many developed countries, the accessibility of antibiotics is strictly striped by insisting that no antibiotics are distributed without written prescription by physician or dispensed by pharmacists. However, in other countries, antibiotics are sold without prescription [8]. In Africa, the occurrence of antibiotic resistance differs among different countries and such incidence not only depends upon the absence of knowledge and alertness towards the development of resistant strain of bacteria but also depend upon unsuitable drug usage policy in the countries [9].…”
Section: Introductionmentioning
confidence: 99%
“…Over-The-Counter (OTC) drugs commonly referred to as non-prescription drugs, are medicines that can be bought without a doctor's prescription. They are extensively offered at supermarkets, pharmacies, and quick-service restaurants [1]. These medications are used to treat some common health issues, including pain, headaches, colds, and allergies [1].…”
Section: Introductionmentioning
confidence: 99%
“…They are extensively offered at supermarkets, pharmacies, and quick-service restaurants [1]. These medications are used to treat some common health issues, including pain, headaches, colds, and allergies [1]. OTC medications can be beneficial for treating minor health issues or relieving symptoms, but they should always be taken carefully and according to the directions on the packaging.…”
Section: Introductionmentioning
confidence: 99%